GRAND DESIGN PEMBANGUNAN PUSAT STUDI ARSIP PENEGAKAN HUKUM TINDAK PIDANA KORUPSI SEBAGAI PUSAT UNGGULAN (CENTER OF EXCELLENCE) ARSIP NASIONAL REPUBLIK INDONESIA: Array - Azmi Azmi (Jurnal Kearsipan, 2017)
The collection of archives on the law enforcement of criminal acts of corruption is factual information which is kept at the National Archives of the Republic of Indonesia (ANRI). They can be used by public as a reference and an area of academic interest. As a National Archive, ANRI is to manage the archives both as a collective memory and a source of knowledge. Moreover, ANRI also should be responsible for giving full access to public for these archives. Generally, ANRI has done all stages of the archives management in accordance with the Number 43 Year 2009 Act on Records and Archives Administration. The stages are acquisition, arrangement and description, preservation, and access of archives. However, in doing the last stage, ANRI needs to have a center of Excellence (CoE). In this research, the writer will discuss on the Grand Design of the Center of Excellence of the collection of the archives on the law enforcement of criminal acts of corruption. This is a qualitative research with a social approach that is used to describe more detail on the phenomena of archives management at ANRI through the establishment of the center of excellence for archives access. Arsip statis penegakan hukum tindak pidana korupsi di Arsip Nasional Republik Indonesia (ANRI) merupakan rekaman informasi faktual yang dapat digunakan sebagai rujukan dan kepentingan akademis. Sebagai lembaga kearsipan, ANRI wajib mengelola arsip statis penegakan hukum tipikor sebagai memori kolektif dan sumber pengetahuan, sehingga dapat diaksesdan dimanfaatkan publik dengan tingkat aksesibilitas tinggi. ANRI secara umum telah melakukan semua tahapan pengelolaan arsip statis untuk kepentingan publik sebagaimana diamanatkan UU Nomor 43 Tahun 2009 tentang Kearsipan, mulai dari tahap akuisisi,pengolahan, preservasi, dan akses arsip statis. Namun demikian, ANRI belum secara khusus memiliki pusat unggulan (Center of Excellence/CoE) aksesibilitas arsip statis. Penelitianini membahas Grand Design Pembangun Pusat Studi Arsip Penegakan Hukum Tipikorsebagai CoE ANRI. Penelitian dengan pendekatan kualitatif ini merupakan penelitian sosial untuk memberikan gambaran yang lebih jelas mengenai fenomena pengelolaan arsip statis di ANRI melalui pembangunan pusat unggulan (center of excellence) aksesibilitas arsip statis.